The banking crisis, banking policy regimes and the value of a bank - Risto Murto (Bank of Finland, 1995)
This paper studies the value of a bank under different banking policy regimes.As banks run into financial distress, authorities in different countries have used different approaches to deal with the crisis.The Nordic countries provide examples of different policy approaches.The results show that the uncertainty over the banking policy regime and changes in this uncertainty can have a major impact on the value dynamics of bank shares.The model produces moral hazard problems both before and after public sector intervention.On the other hand, bank support can increase the original shareholders' incentive to inject new capital into the bank. The model also implies that the government may have an incentive to cheat the bank's shareholders in order to ensure more capital injections from them.
URN:NBN:fi:bof-20140807154
Keywords: 330